Delivering HIV and TB services amidst the COVID-19 pandemic in Indonesia: a qualitative study of challenges and mitigation strategies - Luh Putu Lila Wulandari; Srila Nirmithya Salita Negara; Siska Dian Wahyuningtias; Yusuf Ari Mashuri; I Wayan Cahyadi Surya Distira Putra; Nasser Fardousi; Riris Andono Ahmad; David Boettiger; Ari Probandari; Yanri Wijayanti Subronto; Virginia Wiseman; Marco Liverani (Journal of Global Health Reports, 2024)
# Background